Payment for ecosystem services in Peru: Assessing the socio-ecological dimension of water services in the upper Santa River basin - Dextre, Rosa María (2022)
Increasing pressures on ecosystems in the Latin American region, as well as the adoption of multilateral conservation commitments, have led to the implementation of instruments that are economic in nature but oriented towards the recovery, conservation, and functioning of ecosystems such as Payment for Ecosystem Services (PES). In the Peruvian Andes, hydro-climatic factors and land-use changes are affecting the capacity of the ecosystems of the glaciated Cordillera Blanca to provide water services, in terms of both quality and quantity, to the main users of the Santa River basin. Thus, this study analyses how the socio-ecological interactions affect, and are affected by, the planned introduction of water-related PES in the Quillcay sub-basin, the most populated sub-basins along the Santa River basin. We use a conceptual model based on the current evolution of the water metabolism approach to integrate into a common language of analysis the multiple dimensions of water: water as an ecological fund, as a service, and as a political asset. To explore the interface of these three domains of analysis we rely on a mixed-method data collection: primary data collection through a stakeholder survey and interviews and a review of information from secondary sources. The result of our case study shows that both the ecological dimension and the social dimension affect on the PES project and vice versa. These complex interactions could result in the design of a mechanism in which not all stakeholders benefit equally. This raises the need to recognise the multidimensional nature of water in the design and implementation of policies, and the importance of identifying processes and barriers which affect the success of these policies without making invisible the direct effect they also have on social-ecological systems.